KETERLAKSANAAN KPL DAN PEMBINAAN DOSEN MUDA BERBASIS LESSON STUDY - Media Agustina; Achmad Supriyanto; Burhanuddin Burhanuddin (Graduate School of Universitas Negeri Malang, 2016)
This study aims at assessing the accomplishment of Lecture and Practice Field (KPL) which its implementation is integrated with young lecturer training based on Lesson Study. This research employed a qualitative methodology. The data collection of this study was using documentation and observation sheet. The data analysis technique in qualitative descriptive study resulted in a description of the implementation of lesson study. The results showed that (1) the time and place of lectures is categorized good, (2) providing students KPL and young lecturers with excellent category, (3) the implementation of Lesson study is categorized excellent, (4) the performance of young lecturers and students of the MPA in learning is categorized excellent, and (5) evaluation conducted is categorized excellent.Penelitian ini bertujuan mengkaji keterlaksanaan Kuliah dan Praktik Lapangan (KPL) yang perlaksanakannya diintergrasikan dengan pembinaan dosen muda berbasis Lesson Study. Penelitian ini merupakan penelitian kualitatif. Pengumpulan data menggunakan dokumentasi dan lembar observasi. Teknik analisis data secara deskriptif kualitatif menghasilkan deskripsi tentang kajian pelaksanaan lesson study. Hasil penelitian menunjukkan bahwa (1) waktu dan tempat perkuliahan dengan kategori baik, (2) membekali mahasiswa KPL dan dosen muda dengan kategori sangat baik, (3) pelaksanaan Lesson study dengan kategori sangat baik, (4) kinerja dosen muda dan mahasiswa KPL dalam pembelajaran dengan kategori sangat baik, dan (5) evaluasi yang dilakukan dengan kategori sangat baik.